Interval valued extension of wendroff type integral inequalities (2009)
In this paper we extend the theory of integral inequalities to interval valued mappings in two independent variables. By this, set inclusions are used instead of partial order relation and this enables us to obtain simultaneous upper and lower bounds instead of a pair of inequalities.